Farmer Satisfaction Analysis on Pseudomonas Fluorescens (PF) Biological Agent Usage of Red Pepper Commodity (A survey conducted at Junrejo Village, Batu) - Dirgantari, Ayuma Septidita; Anindita, Ratya (HABITAT, 2017)
Consumer satisfaction is the level of feeling perceived after using a product or service that is very important for the company. The purpose of this study is to analyze the attributes considered and to analyze the level of satisfaction of chili farmers that use Pseudomonas fluorescens (PF) biological agents. This study uses Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). The results reveal that there are 5 attributes of PF biological agents that the farmers choose, i.e. pest and disease control, eco-friendly, ease of application, instructions manual, and ease of obtaining. The result obtained from the calculation of CSI is 71%, so the chili farmers or the consumer are satisfied with PF biological agents.